Water in Circular Economy and Resilience : The Case of Phnom Penh, Cambodia - World Bank (World Bank, Washington, DC, 2021)
This case study is part of a series prepared by the World Bank’s Water Global Practice to highlight existing experiences in the water sector. The purpose of the series is to showcase one or more Two of the main pillars of a circular economy are resource efficiency and zero (or minimum) waste. By significantly reducing water losses and improving operational efficiency, the Phnom Penh Water Supply Authority (PPWSA) is embracing circular economy principles toward a more sustainable future.of the elements that can contribute toward a Water in Circular Economy and Resilience (WICER) system. This case focuses on the experience of Phnom Penh, Cambodia.